The Impact of Capital Structure on Profitability: An Empirical Analysis of Non-financial Listed Firms in China - Han, Y. (2016)
This study examines the influence of capital structure on profitability of listed firms in China during the period from 2006 to 2015. The study uses secondary data collected from the financial statements of 2,693 non-financial firms listed on Shanghai Stock Exchange and Shenzhen Stock Exchange. The Pooled Ordinary Least Squares Model, the Fixed Effect Model and the Random Effect Model are chosen to analyse panel data in this research. This study shows that in China, firms depend largely on external financing, of which a great proportion appears to be short-term debt. Furthermore, it is suggested that capital structure indicated by total debt to assets ratio has a significantly negative impact on firm’s profitability represented by return on assets. Specifically, for both short-term debt and long-term debt, the results present us with a significantly inverse association with profitability. In other words, for Chinese firms during the analysed period, high leverage indeed has detrimental effects on earnings, no matter which kind of debts being issued.